Effect of Beer and Barley water on some biochemical parameters of Diabetic Male Rats - Al-Rekabi , Assis. Lec. Eman A.; Al-Fartosi , Prof. Dr. Khalid G.; Al-jabery , Assis. Lec. Hanan B.; Al-najjar, Assis. Lec. Salam H. (University of Thi-Qar Journal, 2019)
The present study aimed to investigate the effect of beer and barley water on body weight, blood glucose, cholesterol, triglycerides (TG), aspartate aminotransferase (AST), alanine aminotransferase (ALT), malondialdehide (MDA) and ceroluplasmine (CP) level of diabetic male rats. 2ml from beer and barley water were used and the animals were treatment for 14 days. the results showed a significant decrease in body weight, whereas it explained a significant increase blood glucose, cholesterol, TG, AST, ALT, MDA and CP of the diabetic male rats when compared with control group. the results showed a significant decrease in body weight, whereas it explained a significant increase blood glucose, cholesterol, TG, AST, ALT, MDA and CP of the diabetic male rats treated with alcohol when compared with diabetic male rats and control group. the results showed a significant increase in body weight whereas it explained a significant decrease blood glucose, cholesterol, TG, AST, ALT, MDA and CP of the diabetic male rats treated with barley water when compared with diabetic male rats and control group